The Correlation of Work‐Related Stress, Sleep Quality, and Physical Activity Among Academic Staff in a Nigerian Medical School: A Cross‐Sectional Study - Uzoamaka Nwakaego Akobundu; Sochima Johnmark Obiekwe; Jennifer Ezeigwe; Amaechi Ifeoma Adaigwe; Uchenna Prosper Okonkwo; Ada Jovita Daniel; Christopher Olusanjo Akosile (Lifestyle Medicine)
ABSTRACT Background The interrelationship of stress and sleep disorders has long been established with physical activity (PA) proven effective in their management. Academic staff in medical schools may face heightened stress levels when compared with staff in other disciplines as a result of the rigorous academic environment in medical schools, in addition to other possible work stressors. This study aimed to investigate the levels of stress, sleep disorders, and PA among academic staff at the medical school of Nnamdi Azikiwe University, Awka, Nigeria, and to determine the relationship between these variables. Methods This cross‐sectional study consecutively recruited 92 adult lecturers at the study site. Data were collected using the Short Form of International Physical Activity Questionnaire (IPAQ‐SF), Pittsburgh Quality of Sleep Index (PSQI), and the Health and Safety Work‐Related Stress Questionnaire. Data were analyzed using the Statistical Package for Social Sciences (SPSS) version 26. The Spearman's rank correlation coefficient was used to assess the association between variables at a significance level of 0.05. Results The mean age of the participants was 40.00 ± 7.34 years. The mean score for work‐related stress, sleep quality, and PA was 66.09 ± 6.58, 7.84 ± 3.48 (poor quality), and 1219.34 ± 827.83 (moderate PA), respectively. There was a significant positive correlation between work‐related stress and PA levels (ρ = 0.22, p = 0.03). Also, there was no significant correlation between sleep quality and work‐related stress (ρ = −0.16, p = 0.11) and between work‐related stress and sleep quality (ρ = 0.19, p = 0.06). Conclusion In conclusion, high concerns of work stress, poor sleep quality, and moderate PA were observed among the study participants. Targeted interventions to promote PA, improve sleep hygiene practices, and alleviate work‐related stress among academic staff are recommended.